Refractory mixed proliferative and membranous lupus nephritis treated with the topoisomerase I inhibitor irinotecan as add-on therapy. (4th May 2022) - Biesen, R; Frese-Schaper, M; Enghard, P; Cheng, Q; Hiepe, F; Frese, S
Abstract : Objective: To evaluate the safety and effects of irinotecan, an inhibitor of topoisomerase I, on refractory lupus nephritis. Method: A patient with refractory lupus nephritis under medication with mycophenolic acid, prednisolone, and hydroxychloroquine was treated with add-on low-dose irinotecan. Irinotecan was applied every fourth week at a dose of 50 mg/m 2 for four cycles followed by 100 mg/m 2 for another eight cycles. Renal function and anti-double-stranded DNA antibodies as well as blood count for evaluation of side effects were assessed during the treatment with irinotecan. Results: Before starting the treatment with irinotecan, a urine protein/creatinine ratio of 1298 mg/g was determined. This declined to 613 mg/g after four cycles with 50 mg/m 2 irinotecan and was further reduced to 198 mg/g when using the higher dose of irinotecan. Kidney function remained stable, with creatinine levels of 1.66 mg/dL at the beginning and 1.76 mg/dL at the end of treatment with irinotecan. Importantly, no side effects, such as diarrhoea or neutropenia, were observed during the entire course of treatment. Conclusion: Administration of low-dose irinotecan as add-on medication for the treatment of refractory lupus nephritis was shown to be safe. Clinical trials are needed to determine whether irinotecan can improve kidney function and the outcome of patients with refractory lupus nephritis.